Checkpoint Inhibitor-Induced Colitis-A Clinical Overview of Incidence, Prognostic Implications and Extension of Current Treatment Options - Carmen Portenkirchner; Peter Kienle; Karoline Horisberger (MDPI AG, 2021)
In recent years, anti-tumor immunotherapies have witnessed a major breakthrough with the emergence of immune checkpoint inhibitors (ICIs). However, the use of ICIs has also brought an era of a certain class of adverse events that differ from those of classical chemotherapies and are more reminiscent of autoimmune diseases. This article focuses exclusively on colitis as an irAE with emphasis on vulnerable patient groups, the prognostic significance of colitis, treatment, and new therapeutic approaches that may be applicable. Colitis itself is associated with a favorable oncological outcome of the underlying disease but is as well the most common irAE leading to discontinuation of therapy. Especially in vulnerable patient groups such as IBD patients and elderly patients, colitis occurs more frequently as a side effect. It is precisely in these two patient groups that side effects more often lead to discontinuation of therapy. Therefore, in addition to the current therapy of colitis through immunosuppression, the focus should also be on new forms of therapy of severe colitis, such as fecal transplantation or ileostomy creation.